A Textual Enigma in John Wesley’s Christian Library - Olson, Mark K. (Wesley and Methodist studies, 2026)
This article explores a textual discrepancy between the two editions of John Wesley’s Christian Library. In 1755, Wesley included an extract of William Beveridge’s Private Thoughts Upon Religion in volume 47. Seventy years later Thomas Jackson altered Wesley’s extract by removing material and in its place inserting Wesley’s sermon The Lord Our Righteousness, without any note or footnote alerting the reader of the addition. This article explains in detail the nature of the enigma and offers some possible solutions. But in the end, the enigma remains since we do not have concrete answers.